PENGARUH TEKNOLOGI INFORMASI, SALING KETERGANTUNGAN, DAN STRATEGI BISNIS TERHADAP KINERJA MANAJERIAL DENGAN KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN (SAM) SEBAGAI VARIABEL INTERVENING PADA BANK UMUM DI KOTA PEKANBARU - Khairi, Ardhi; -, Yusrarlaini; Savitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze and gets empirical prove of influence of the effect information technology, interdependent, bussiness strategy, and managerial of accountant system characteristic (SAM) broadscope to performance of managerial. Respondent in this research is manager who work ini general bank in pekanbaru city.The sampling is selected using purposive sampling, data collection method using a questionnaire with the number of manager that the sample of this research was 54 of 32 general bank. This research is a quantitative model with data analysis method using SPSS software version 18.00 to process data.The result of this research indicate the effect information technology and interdependent have a significant effect on managerial of accountant system characteristic (SAM) broadscope, but not for business strategy. So, accountant system characteristic (SAM) broadscope is an intervening variable for information technology and interdependent, but not as intervening variable for bussiness strategy. Keywords: information technology, interdependent, bussiness strategy, managerial of accountant system characteristic (SAM) broadscope, performance of managerial